De l’école-sanctuaire à l’école sans murs - André Pachod (Recherches en Éducation)
The French school system is being experienced in a time-space, bearing material or symbolic boundaries. The so-called ‘behind the walls’ school can be defined, with reference to the religious language, as a sanctuary and an enclosure which separate, protect, regulate. It thus conveys three conceptions: the school as a sanctuary, the school as an academic enclosure, the educational form. The evolutions of society, school education, teaching and learning methodologies continue to question these notions. In a cognitive and neo-liberal society, school education needn’t have any walls: distance education, virtual classrooms, MOOC, etc. These developments question the future of the school in its form, methods and above all its current and future purposes.